Evaluation of the Effect of Water on Three Different Light Cured Composite Restorative Materials Stored in Water: An In Vitro Study - Basawaraj Biradar; Sudharani Biradar; Arvind MS (Hindawi Limited, 2012)
Objectives. The objective of this in vitro study was to investigate whether weight gain or loss in the three different composites occurs due to water absorption when they are stored in water. Methods. The composite restorative materials selected for this study included a microfine hybrid (Synergy) and two nanofilled composite restorative materials (Ceram X and Filtek Supreme Ultra). Twenty specimens of each material were fabricated of each composite material. Group A: Filtek Supreme Ultra, Group B: Synergy, Group C: Ceram X. Then all the specimens were stored in 10 ml Distilled water containing test tubes and placed in incubator at 37°C for six weeks. The weight changes of these specimens were measured daily for the first week and later once a week for next five weeks by using an electrical analytical balance. Results. The data was analyzed by one-way analysis of variance and Student's t test. All groups showed maximum amount of water absorption in the first week than gradual decrease in the water absorption from the second to the sixth week, as compared to the first week and there is no statistically significant difference between the groups tested. Conclusion. All the composite restorative material absorbs some amount of water. The water absorption of the composite may decrease the physical and mechanical properties of the composites; hence it is necessary to consider the type of the material before starting the treatment.